Consider the recurrence relation f n + 1 ( x ) = x + 2 f n ( x ) for n = 1 , 2 , 3 , … and f 1 ( x ) = 3 x .
Find the sum of all possible roots of x = f n ( x ) for all positive integer n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Write easyly 2 1 ( x 2 − x ) = x following x=0 and x=3.
@Prakhar Bindal - Try this one out
@Pi Han Goh - You changed my problem language now what about my solution. It does not go well with the new language
Log in to reply
It's wrong from the start. You have only shown that the answer is 3 when n → ∞ .
Log in to reply
It was correct according to previous language
Log in to reply
@Anubhav Tyagi – No, it's not. Tell me how you've shown (in your solution) that the answer is 3 regardless of the value of n .
Log in to reply
@Pi Han Goh – You may check by putting for n= any integer
Log in to reply
@Anubhav Tyagi – Are you saying you've done proof by exhaustion for all positive integers n ?
Log in to reply
@Pi Han Goh – Yes any doubts
Log in to reply
@Anubhav Tyagi – First of all, you have not shown that in your solution. And second of all, you can't perform "proof by exhaustion" for an infinitely many number of cases because it's an impossible task.
Log in to reply
@Pi Han Goh – It has got 3 upvotes which means that people might have understood it.
Log in to reply
@Anubhav Tyagi – I could upvote it too, does it mean that your solution is correct?
Log in to reply
@Pi Han Goh – You won't cause you will never learn to appreciate
Log in to reply
@Anubhav Tyagi – This is a very fruitful discussion.
Log in to reply
@Pi Han Goh – What do you mean?
Log in to reply
@Anubhav Tyagi – He is being sarcastic.
Please be respectful of moderators, they have to take decisions in behalf of the community, which is not an easy task.
Log in to reply
@Agnishom Chattopadhyay – Are you saying that I am being sarcastic?
Log in to reply
This is a very fruitful discussion
That is a sarcastic comment.
Problem Loading...
Note Loading...
Set Loading...
⇒ x = x + 2 x ⇒ x = 0 , 3 x = f n ( x ) = x + 2 f n − 1 ( x ) = x + 2 x + 2 f n − 2 ( x ) Hence we write as: x = x + 2 x + 2 x + 2 ⋯ + 2 3 x ( n times ) x = x + 2 x + 2 x + 2 ⋯ + 2 x + 2 x ( n times ) Replace underlined x from equation (1) x = x + 2 x + 2 x + 2 ⋯ + 2 x + 2 x ( 2 n times ) Replace underlined x from equation (1) x = x + 2 x + 2 x + 2 ⋯ + 2 x + 2 x ( 3 n times ) Replace underlined x from equation (1) x = x + 2 x + 2 x + 2 ⋯ + 2 x + ⋯ ( k → ∞ lim k times ) ( 1 )